2014
DOI: 10.1021/jp502386e
|View full text |Cite
|
Sign up to set email alerts
|

Micelles and Aggregates of Oxyethylated Isononylphenols and Their Extraction Properties near Cloud Point

Abstract: We used nuclear magnetic resonance (NMR) spectroscopy and dynamic light scattering (DLS) techniques to study the structural and dynamic properties of micellar solutions of nonionic surfactants of a homologous series of oxyethylated isononylphenols--C9H19C6H4O(C2H4O)(n)H, where n = 6, 8, 9, 10, or 12--in a wide range of temperatures, including cloud points. The radii of the micelles and aggregates, as well as their compositions at different concentrations of surfactant, were determined. Using aqueous phenol sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The dynamic and structural properties of aqueous solutions of neonols were studied in detail by us earlier. Relations were obtained expressing the dependence of the cloud point on the number of oxyethylene groups in neonol molecules at a constant concentration of neonols in solutions with C = 1 wt %. The hydration of oxyethylene chains was studied and it was shown that ∼3 to 4 water molecules bound to one oxyethylene group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic and structural properties of aqueous solutions of neonols were studied in detail by us earlier. Relations were obtained expressing the dependence of the cloud point on the number of oxyethylene groups in neonol molecules at a constant concentration of neonols in solutions with C = 1 wt %. The hydration of oxyethylene chains was studied and it was shown that ∼3 to 4 water molecules bound to one oxyethylene group.…”
Section: Resultsmentioning
confidence: 99%
“…The hydration of oxyethylene chains was studied and it was shown that ∼3 to 4 water molecules bound to one oxyethylene group. The sizes of micelles of water-soluble neonols AF9-8,9,10,12 were determined by NMR and dynamic light scattering analyses in the temperature range from 25 °C to the corresponding cloud points . It was found that the effective hydrodynamic radii of micelles of individual neonols AF9-8,9,10,12 at C = 1 wt % in aqueous solutions monotonically increase with temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Based on experimental data [22,23] of the SDC of the neonols, the effective hydrodynamic radii of micelles and aggregates were calculated using the Stokes-Einstein relation:…”
Section: Radii Of Micellesmentioning
confidence: 99%
“…The objects of study are oxyethylated alkyl phenols (neonols). To calculate the aggregation numbers, measurements of the selfdiffusion coefficients (SDC) were used [22,23], on the basis of which the effective radii of micelles and aggregates were determined using the Stokes-Einstein relation and the aggregation numbers were calculated.…”
Section: Introductionmentioning
confidence: 99%
“…[6,9,13] Nuclear magnetic resonance (NMR), an essentially nonperturbing and noninvasive method, is one of the most important methods for characterizing surfactant systems. [5,[14][15][16][17] NMR chemical shifts of surfactant groups and self-diffusion coefficients of surfactants molecules and aggregates provide qualitative and quantitative information about mobility and, indirectly, about the structure of aggregates. CMC measured by the surface tension method provides only the concentration at which micelles start to form, while diffusion data provided by NMR give additional information about the concentration of the weighted average of the monomolecular surfactant and those included in the micelles.…”
Section: Introductionmentioning
confidence: 99%